2014
DOI: 10.1128/genomea.00990-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Virulent Strain AUSTRAL-005 of Piscirickettsia salmonis, the Etiological Agent of Piscirickettsiosis

Abstract: We report here the draft genome sequence of a lethal pathogen of farmed salmonids, Piscirickettsia salmonis strain AUSTRAL-005. This virulent strain was isolated in 2008 from Oncorhynchus mykiss farms, and multiple genes involved in pathogenicity, environmental adaptation, and metabolic pathways were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…1). Moreover, we have demonstrated that all characterized P. salmonis strains have flagellar genes and share the same genetic organization (Eppinger et al 2013, Bohle et al 2014, Yañez et al 2014, Pulgar et al 2015. Our results suggest that P. salmonis has the potential to develop a flagellum controlled by this transcriptional cascade.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…1). Moreover, we have demonstrated that all characterized P. salmonis strains have flagellar genes and share the same genetic organization (Eppinger et al 2013, Bohle et al 2014, Yañez et al 2014, Pulgar et al 2015. Our results suggest that P. salmonis has the potential to develop a flagellum controlled by this transcriptional cascade.…”
Section: Discussionmentioning
confidence: 57%
“…Once the genes were confirmed, the CLC Main Workbench 5 software (www.clcbio.com) was used to complement sequence analysis, specifically for accurate alignments, and to determine the putative operon organization of flagellar genes in P. salmonis. Finally, flagellar gene organization was compared between different P. salmonis strains using recently reported genomes (Eppinger et al 2013, Bohle et al 2014, Yañez et al 2014, Pulgar et al 2015.…”
Section: Screening Of the Piscirickettsia Salmonis Genomementioning
confidence: 99%
“…salmonis [75]. The results of the transcriptome analysis of our isolate revealed two pathways for iron uptake: through siderophores and iron ferrous uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Most crucial would be a formal polyphasic approach comparing TRLO, P. salmonis and, if possible, P. salmonis-like organisms (Chen et al 2000a,b, Mauel et al 2003, McCarthy et al 2005 incorporating methods secondary to 16S rDNA or multilocus sequence analysis such as DNA:DNA hybridisations (Rosselló-Mora & Amann 2001, Stackebrandt et al 2002, Tindall et al 2010 or whole genome sequence comparison (Whitman 2015). The latter is now very realistic given that 2 P. salmonis genomes have already been sequenced and published (Eppinger et al 2013, Yañez et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Most crucial would be a formal polyphasic approach comparing TRLO, P. salmonis and, if possible, P. salmonis-like organisms (Chen et al 2000a,b, Mauel et al 2003, McCarthy et al 2005 incorporating methods secondary to 16S rDNA or multilocus sequence analysis such as DNA:DNA hybridisations (Rosselló-Mora & Amann 2001, Stackebrandt et al 2002, Tindall et al 2010 or whole genome sequence comparison (Whitman 2015). The latter is now very realistic given that 2 P. salmonis genomes have already been sequenced and published (Eppinger et al 2013, Yañez et al 2014.In summary, evidence is presented showing that TRLO comprises a serotypically diverse group of novel bacteria capable of in vitro growth in an intracellular or extracellular environment. Evidence of phylogenetic, phenotypic and antigenic differences justifies the sustained use of the TRLO name and separation from P. salmonis, but further detailed analyses are required for formal taxonomic placement of TRLO.…”
mentioning
confidence: 99%